Short-range and long-range solvent effects on charge-transfer-to-solvent transitions of I- and K+ I- contact ion pair dissolved in supercritical ammonia - Sciaini, G. (2007)
Vertical excitation and electron detachment energies associated with the optical absorption of iodide ions dissolved in supercritical ammonia at 420 K have been calculated in two limiting scenarios: as a solvated free I- ion and forming a K+ I- contact ion pair (CIP). The evolution of the transition energies as a result of the gradual building up of the solvation structure was studied for each absorbing species as the solvent's density increased, i.e., changing the N H3 supercritical thermodynamic state. In both cases, if the solvent density is sufficiently high, photon absorption produces a spatially extended electron charge beyond the volume occupied by the solvated solute core; this excited state resembles a typical charge-transfer-to-solvent (CTTS) state. A combination of classical molecular dynamics simulations followed by quantum mechanical calculations for the ground, first-excited, and electron-detached electronic states have been carried out for the system consisting of one donor species (free I- ion or K+ I- CIP) surrounded by ammonia molecules. Vertical excitation and electron detachment energies were obtained by averaging 100 randomly chosen microconfigurations along the molecular dynamics trajectory computed for each thermodynamic condition (fluid density). Short- and long-range contributions of the solvent-donor interaction upon the CTTS states of I- and K+ I- were identified by performing additional electronic structure calculations where only the solvent interaction due to the first neighbor molecules was taken into account. These computations, together with previous experimental evidence that we collected for the system, have been used to analyze the solvent effects on the CTTS transition. In this paper we have established the following: (i) the CTTS electron of free I- ion or K+ I- CIP presents similar features, and it gradually localizes in close proximity of the iodine parent atom when the ammonia density is increased; (ii) for the free I- ion, the short-range solvent interaction contributes to the stabilization of the ground state more than it does for the CTTS excited state, which is evidenced experimentally as a blueshift in the maximum absorption of the CTTS transition when the density is increased; (iii) this effect is less noticeable for the K+ I- ion pair, because in this case a tight solvation structure, formed by four N H3 molecules wedged between the ions, appears at very low density and is very little affected by changes in the density; (iv) the long-range contribution to the solvent stabilization can be neglected for the K+ I- CIP, since the main features of its electronic transition can be explained on the basis of the vicinity of the cation; (v) however, the long-range solvent field contribution is essential for the free I- ion to become an efficient CTTS donor upon photoexcitation, and this establishes a difference in the CTTS behavior of I- in bulk and in clusters. © 2007 American Institute of Physics.